The Effect Of Work Division, Employee Development, And Supervision On Employee Work Quality At The Protocol And Leadership Communication Division, Regional Secretariat Of Lahat Regency - Nabillah Rahma Yanti Putri; Harun Samsuddin; Darmin Darmin (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine and analyze the effect of division of labor, guidance, and supervision on the work quality of employees in the Protocol and Leadership Communication Division of the Regional Secretariat of Lahat Regency, both partially and simultaneously. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees and analyzed using multiple linear regression analysis to examine the influence of the independent variables on the dependent variable. The results revealed that (1) division of labor did not have a positive partial effect on employee work quality, indicating that the existing allocation of tasks had not become a major factor in improving work quality; (2) guidance had a positive partial effect on work quality, meaning that better guidance contributes to higher work quality; (3) supervision had a positive partial effect on work quality, showing that effective supervision can improve the quality of work performance; and (4) division of labor, guidance, and supervision simultaneously had a positive effect on employee work quality. Therefore, improving employee work quality can be achieved through the optimization of guidance and supervision supported by an appropriate and well-coordinated division of labor.